Rapidly Progressive Multisystem Autoimmune Disease in an Adolescent Male: A Fatal Case of Overlapping ANCA-Associated Vasculitis and Systemic Lupus Erythematosus Complicated by Acute Kidney Injury and Multiorgan Failure (Bangladesh Journal of Medical Science, 2026)
Background Rapidly progressive autoimmune diseases in pediatric populations pose substantial diagnostic and therapeutic challenges due to aggressive clinical courses, multisystem involvement, and frequent overlap between immunological syndromes. The coexistence of systemic lupus erythematosus (SLE) and ANCA-associated vasculitis in adolescents is rare and associated with severe renal injury, cardiovascular complications, and high mortality. Objective To describe a fatal case of fulminant multisystem autoimmune disease in a 14-year-old male characterized by rapidly progressive glomerulonephritis, severe cardiac dysfunction, respiratory failure, and sepsis. Methods A retrospective descriptive analysis was performed using hospital records from tertiary referral centers. Clinical history, laboratory and immunological findings, imaging studies, specialist consultations, treatment strategies, and disease progression were systematically reviewed. Results The patient developed acute kidney injury stage F according to RIFLE criteria in the context of overlapping SLE and ANCAassociated vasculitis. The disease course was complicated by progressive multiorgan failure involving renal, cardiac, pulmonary, hepatic, and hematopoietic systems. Despite renal replacement therapy, immunosuppressive treatment, and advanced intensive care support, the patient died due to refractory metabolic acidosis, respiratory failure, and septic shock. Conclusion This case highlights the extreme aggressiveness of pediatric autoimmune overlap syndromes and emphasizes the importance of early immunological evaluation and prompt initiation of targeted therapy. The fatal outcome reflects both the fulminant nature of the disease and current limitations in managing advanced multisystem autoimmune involvement.BJMS, Vol. 25 No. 02 April’26 Page: 648-654